TI_GERICHTE 35.2022.45 vom 14. November 2022 , Esigibilità contestata. Arti superiori. Problematica neurologica. Rinvio per perizia ex art. 44 LPGA - TI Tribunale d'appello (2022)
Esigibilità contestata. Arti superiori. Problematica neurologica. Rinvio per perizia ex art. 44 LPGA